Narasi Islamisme Dan Politik Identitas: Pola Penyebaran dan Islam Radikal di Wilayah Lampung - Tasman, Tasman; A.V, Lazuardi (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2024)
This article discusses the spread of Islamism in Lampung Province. In the research, it was found that the narrative of Islamism, which uses violence such as suicide bombings, was rejected by the informants interviewed in Lampung. The research uses observation and interview methods, the potential for violence comes from other very potential issues; namely the strengthening of ethnic identity and mixing with religious identity between immigrant groups (transmigrants) and local indigenous residents which ends in conflict between groups, the issue of robbery which is more motivated by socio-economic factors. The issue of radicalization of religious groups is caused by loose cultural ties between ethnic groups and other local issues such as regional elections and local political struggles. These issues have resulted in a lot of social violence, mass judgment, clashes between teenagers, and clashes between villages, which started from trivial problems such as problems, theft, and women. These themes are current in society and tend to lead to ethno-centrism. Because Lampung has a long history of transmigration, the presence of migrant communities through an imperfect assimilation process causes the weakening of social ties and solidarity between cultures, triggering the emergence of radicalism. Religion is often used as a justification for ongoing conflicts. Therefore, the argument for the emergence of radicalism and terrorism has a special character for the context of Lampung society.